2023
DOI: 10.3390/ijms24021708
|View full text |Cite
|
Sign up to set email alerts
|

Multi-Step Extracellular Matrix Remodelling and Stiffening in the Development of Idiopathic Pulmonary Fibrosis

Abstract: The extracellular matrix (ECM) of the lung is a filamentous network composed mainly of collagens, elastin, and proteoglycans that provides structural and physical support to its populating cells. Proliferation, migration and overall behaviour of those cells is greatly determined by micromechanical queues provided by the ECM. Lung fibrosis displays an aberrant increased deposition of ECM which likely changes filament organization and stiffens the ECM, thus upregulating the profibrotic profile of pulmonary cells… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 67 publications
0
6
0
Order By: Relevance
“…However, pulmonary fibrosis is a severe disease that affects the ECM in the lungs, stiffening over time, with patients having a short lifespan after diagnosis. Recent studies in the fibrotic rat lung have shown that the nanomechanical properties of the ECM change, inducing stiffening, and how the fibrotic architecture plays a role in it 38,244 …”
Section: Respiratory Diseasesmentioning
confidence: 99%
See 1 more Smart Citation
“…However, pulmonary fibrosis is a severe disease that affects the ECM in the lungs, stiffening over time, with patients having a short lifespan after diagnosis. Recent studies in the fibrotic rat lung have shown that the nanomechanical properties of the ECM change, inducing stiffening, and how the fibrotic architecture plays a role in it 38,244 …”
Section: Respiratory Diseasesmentioning
confidence: 99%
“…Recent studies in the fibrotic rat lung have shown that the nanomechanical properties of the ECM change, inducing stiffening, and how the fibrotic architecture plays a role in it. 38,244…”
Section: Respiratory Diseasesmentioning
confidence: 99%
“…Studying the biomechanical behavior of bones helps to understand the mechanisms of fracture healing and how the healing process can be accelerated by surgical or other interventions. Lung diseases, especially dyspnea, often involve problems with respiratory airflow, lung tissue elasticity, and thoracic cavity mechanics (Júnior et al, 2023). Understanding these mechanical properties is important in the diagnosis and treatment of lung diseases.…”
Section: Afm Mechanics and Medical Challengesmentioning
confidence: 99%
“…Traditionally, when wound healing pathways are impaired, activated fibroblasts continue to recruit and accumulate, forming fibrotic areas in the lung. This faulty wound-healing process can cause ongoing remodeling of IPF and damage the extracellular matrix (ECM), leading to the progression of IPF and end-stage lung disease [ 17 ]. Cysteine cathepsins are usually found in lysosomes, where they are involved in intracellular protein turnover and are currently considered to be critical players in ECM remodeling in vivo [ 18 ].…”
Section: Introductionmentioning
confidence: 99%